(untitled) (Annals of Medical Research, 2023)
Aim: Emergent operation is the accepted standart therapy of acute appendicitis. But medical therapy is an emerging solution for acute appendicitis. We aimed to publish the conservative treatment experience of Inonu University Medical School, Department of General Surgery. Materials and Methods: Between January 2020 and January 2022, patients with suspicious acute appendicitis were scanned by the hospital medical record system. Patients that had an emergent operation were excluded. Remaining patients were reviewed. All patients were followed up both by the Inonu University and Turkish Health Ministry medical record system. Patient demographics and clinical data were analyzed retrospectively. Results: Fifteen patients were detected within the 2 years period that received medical therapy for acute appendicitis. Median age was 32.0 (min:19 - max:70), median appendix diameter was 7.2 mm (min:5.5 - max:11.0). One patient was died due to Non-Hodgkin Lymphoma after 16 days of diagnosis of acute appendicitis. None of the patients required an operation during surveillance. Most frequent reasons for conservative treatment were probability of pelvic inflammatory disease, inflammatory intestinal disease and urinary tract infections. Conclusion: While some comorbidities may accompany with acute appendicitis such as cardiac and systemic haematologic diseases, some of them mimic acute appendicitis such as pelvic inflamatory disease or inflamatory bowel diseases. Elder patients, who have a suspicious case, may benefit from antibiotherapy. Low crp and neutrophilia counts are the predictors of uncomplicated appendicitis and medical treatment. More patients with an appendectomy history need to be evaluated on this aspect.